E-Marketing Analysis of Furniture Products at CV. Jasmine Maddani Tolengas Sumedang - Kurniasih, Nining; Munggaran, Rani (SINTESA, 2024)
Sales at CV. Jasmine Maddani Tolengas Sumedang is experiencing fluctuating sales conditions, which is due to the many competitors that have sprung up in Sumedang Regency, lack of advertising promotions, and the impact of the co-19 pandemic. This study aims to find out how the implementation of E-Marketing on CV. Jasmine Maddani and to find out how to solve E-Marketing problems on CV. Jasmine Maddani. The research method used is a qualitative method with a descriptive type of research. The research subjects are owners, account operators, and employees at CV. Jasmine Maddani. Techniques and data collection used in this study are observation, interviews and documentation. The techniques and data analysis used are data collection, data reduction, data presentation and conclusion. The results of this study are CV. Jasmine Maddani has implemented communication and service from the very beginning and has been running very effectively because she was able to get a good response from consumers. In business transactions CV. Jasmine Maddani has implemented developments in banking, namely via transfers to make transactions easier with consumers. On online CV. Jasmine Maddani uses social media such as Shoppe, Instragram, Facebook and Email. The most dominant application is Instragram. CV. Jasmine Maddani only uses email for employee recruitment needs, sending interior designs to consumers. CV. Jasmine Maddani uses Facebook for media as a promotion. CV. Jasmine Maddani has implemented Shoppe but her sales are very low because account owners and operators still have a lot to learn how to increase sales on the marketplace